A concise history of world population - Livi Bacci, Massimo (Blackwell, 1997)
This book describes and explains the history of human population. It examines the changing patterns of its growth, and the effects upon it of migrations, wars, disease, technology and culture. Since its publication in 1992 it has become the most widely read account of the subject, valued for its contemporary recasting of theory, for its informative and accessible style, and for its reasoned treatment of issues crucial to the future of every species.